Nghiên cứu phản ứng isome hóa n-hexan trên xúc tác Pt/gamma-Al2O3 - Trịnh, Nguyễn Hữu (Vietnam Journal of Chemistry, 2014)
At the present, in order to increase octan number the izomerization of hydrocarbon has been studied in the world. Amongs metals and metal oxides on carriers, Pt on the alumina carrier is used most widely owing to the advantages such as thermal stability, high activity and high selectivity etc. The conversion and selectivity of the izomerization depend on the catalysts (the composition of the catalysts, the structure of the carriers, the distribution of metal, the acidity, the catalytic activity of the catalysts) and the reaction condition (temperature, volume flow, carrier gases ...).